A new setup to study the influence of plant growth on the consolidation of dredged cohesive sediment - Barciela-Rial, Maria; Saaltink, Remon M.; van Kessel, Thijs; Chassagne, Claire; Dekker, Stefan C.; de Boer, Hugo J.; Griffioen, Jasper; Wassen, Martin J.; Winterwerp, Johan C. (Frontiers in Earth Science, 2023)
Dredged cohesive sediment is progressively being used for wetland construction. However, little is known about the effect of plant growth during the self-weight consolidation of this sediment. In order to check the feasibility of such a study, a new experimental set-up has been constructed. As an example, the effect of Phragmites australis on the consolidation and drainage of dredged sediment from Lake Markermeer, the Netherlands was investigated. The changes in pore water pressures at 10 cm depth intervals during a 129-day period in a column with and without plants was measured, while the water level was fixed. Water loss via evaporation and plant transpiration was measured using Mariotte bottles and the photosynthetic processes – including plant transpiration – were measured with a LICOR photosynthesis system. The results show that several processes initiated by Phragmites. australis interfere with the physical processes involved in sediment drainage and consolidation. Phragmites australis effectively altered the pore pressure gradient via water extraction, especially between 40 and 60 cm from the bottom of the column. In this zone, daily cycles in pore pressures were observed which could directly be linked to the diurnal cycle of stomatal gas exchange. On average, water loss via evaporation and transpiration of leaves of Phragmites australis amounted to 3.9 mm day-1, whereas evaporation of bare soil amounted on average to 0.6 mm day-1. The depth-averaged hydraulic conductivity increased on average by 40% in presence of Phragmites. australis. This pilot experiment confirms that the pressures sensors coupled with the new set-up enable to study pore pressure development over time and to link the effect of plant growth with alterations in water pressures profiles. A more systematic study with this set-up will in the future enable to quantify the effects of plant growth on consolidation.